2018
DOI: 10.1177/2010105818760045
|View full text |Cite
|
Sign up to set email alerts
|

Return on investment in blended advanced cardiac life support training compared to face-to-face training in Singapore

Abstract: Background: Internet adoption during the past decade has provided opportunities for innovation in advanced cardiac life support (ACLS) training. With pressure on budgets across health care systems, there is a need for more cost-effective solutions. Recently, traditional ACLS training has evolved from passive to active learning technologies. The objective of this study is to compare the cost, cost-savings and return on investment (ROI) of blended ACLS (B-ACLS) and face-to-face ACLS (F-ACLS) in Singapore. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Results from two studies showed that the blended learning course is superior to the traditional course in terms of cost reductions. 39. , 42.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from two studies showed that the blended learning course is superior to the traditional course in terms of cost reductions. 39. , 42.…”
Section: Resultsmentioning
confidence: 99%
“…A study from Singapore showed 61% of savings over 5 years if blended ALS courses were to be used instead of a traditional approach. 39 The estimated annual costs to conduct ALS courses via blended learning and traditionally were S$43,467 and S$72,793, respectively. Furthermore, a study of the RCUK e-ALS course reported total costs per participant as $438 for blended learning and $935 for traditional learning.…”
Section: Resultsmentioning
confidence: 99%
“…The transfer of learning to the clinic, impact on mortality, or costs have been analyzed. There is evidence that the mixed methodology provides significant savings for the provider [ 34 , 35 ]. In other research studies, it could be feasible to approach the comparison of didactic methodologies in ALS training contemplating the acquisition of non-technical skills.…”
Section: Discussionmentioning
confidence: 99%
“…The review included 8 studies. 368,[372][373][374][375][376][377][378] For the outcome of ALS knowledge (after the intervention), 2 studies found significantly higher scores in the blended-learning group, 372,378 whereas the remainder of the studies found no significant difference between the groups. 368,373,377 There was no significant difference between groups for 1 study at 7 months.…”
Section: Adult Alsmentioning
confidence: 99%
“…Two studies found a notable financial benefit for teaching ALS through a blended-learning approach. 374,377…”
Section: Education Implementation and Teamsmentioning
confidence: 99%